Providing Comfort through Music to People Amidst the COVID-19 Pandemic as a Humanitarian Disaster - Situmorang, Dominikus David Biondi 19XX- (Journal of pastoral care & counseling, 2021)
Hopefully, through this article, mental health workers, such as counselors, psychologists, psychiatrists, nurses, doctors, religious leaders, and social workers, can consider music as a good alternative in the midst of this COVID-19 pandemic. It is hoped that mental health workers who are currently struggling to care for everyone's psychological health in their respective countries can provide comfort through collective music activities.